2015
DOI: 10.1039/c4cp05308g
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of allylic radicals that impact molecular weight growth kinetics

Abstract: The reactions of allylic radicals have the potential to play a critical role in molecular weight growth (MWG) kinetics during hydrocarbon oxidation and/or pyrolysis. Due to their stability (when compared to alkyl radicals), they can accumulate to relatively high concentrations. Thus, even though the rate coefficients for their various reactions are small, the rates of these reactions may be significant. In this work, we use electronic structure calculations to examine the recombination, addition, and abstracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 66 publications
(107 reference statements)
3
71
1
Order By: Relevance
“…A similar result could be obtained by lowering the preexponential factor of , but a larger barrier is in better accord with theoretical values . At 1000 K, our rate constant for ring closure ( k −3 ) is 3× to 7× larger than values estimated by Wang et al (Table ). In our model, the use of a smaller value of k −3 would require a corresponding reduction in k 4 (beta scission of allyl) to fit the Tsang and Walker data.…”
Section: Resultssupporting
confidence: 91%
“…A similar result could be obtained by lowering the preexponential factor of , but a larger barrier is in better accord with theoretical values . At 1000 K, our rate constant for ring closure ( k −3 ) is 3× to 7× larger than values estimated by Wang et al (Table ). In our model, the use of a smaller value of k −3 would require a corresponding reduction in k 4 (beta scission of allyl) to fit the Tsang and Walker data.…”
Section: Resultssupporting
confidence: 91%
“…As the concentrations of the higher olefins build up, so do the concentrations of the resonantly stabilized allylic radicals. Recently Wang et al 35 have shown that these allylic radicals have important pathways leading to molecular weight growth. Additionally the stability of the allylic radicals allows for the buildup of their concentrations, this leads to a decrease in the decomposition rate of pentane.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The ring‐strain energies are also provided; the energy barriers for the corresponding bimolecular H‐atom abstraction reactions are from previous studies 23. 24…”
Section: Resultsmentioning
confidence: 99%
“…This is primarily due to the bimolecular component of the activation energy, which is about 16 kcal mol −1 for the H‐atom abstraction by a primary allylic radical from a secondary allylic site 23. 24 The analogous bimolecular abstraction reaction of an alkyl radical has an activation energy of around 12 kcal mol −1 35. With the exceptions of reactions 4.1 and 5.1, the ring‐strain energies are similar to those for the corresponding reactions in Scheme or .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation